Comparison of Shock Wave Parameters of in Situ ESWL & ESWL After Push Back for Upper Ureteric Calculi (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background: To compare the shock wave parameters of in situ ESWL & ESWL after push back for upper ureteric calculi.Methods: This hospital based prospective study was carried out in the Department of Urology, Bangabandhu Sheikh Mujib Medical University (BSMMU) Dhaka from January 2006 to December 2006. For this study, 90 patients were selected according to the selection criteria. They were divided into two groups. Group 1 included 50 patients treated by in situ ESWL and group 2 included 40 patients treated by push back and ESWL. For statistical analysis, student’s t- test & chi-square test were performed.Results: In group 1 and in group 2 patients mean age were 34.86±11.74 years and 35.12± 12.48 years respectively. In group 1: Over all clearance of calculi was 92.86% in 1cm stones and 86.36% in 1cm stones (p>0.05). In group 2: Total clearance was 100% in stones 0.05). Although clearance rate was higher in push back group it was not statistically significant (92.5% Vs.90%) (p>0.05). Number of ESWL session in case of 0.05). Considering the requirement of shock wave number, less shock wave were required in group 2 (1757.50 ± 255.09) than group 1 (1994 ± 449.22) (p < 0.01). Mean energy needed in group I was 5.07±0.81 and in group 2 it was 4.63±0.48 (p